Prognostic significance of preoperative neutrophil-to-lymphocyte ratio in surgically resected schwannomas - Takahara, Kento; Tamura, Ryota; Kuranari, Yuki; Karatsu, Kosuke; Akiyama, Takenori; Toda, Masahiro (Frontiers in Oncology, 2023)
Objective The goal of schwannoma resection is to control the tumor while preserving neurological function. Schwannomas have a variable postoperative growth pattern, therefore preoperative prediction of a schwannoma’s growth pattern is favorable. This study aimed to examine the relationship between preoperative neutrophil-to-lymphocyte ratio (NLR) and postoperative recurrence and retreatment in patients with schwannoma. Methods We retrospectively examined 124 patients who underwent schwannoma resection in our institution. Associations between preoperative NLR, other patient and tumor characteristics, and tumor recurrence and retreatment were analyzed. Results Median follow-up was 2569.5 days. Postoperative recurrence occurred in 37 patients. Recurrence that required retreatment occurred in 22. Treatment-free survival (TFS) was significantly shorter in patients with NLR ≥2.21 (P = 0.0010). Multivariate Cox proportional hazards regression showed that NLR and neurofibromatosis type 2 were independent predictors of retreatment (P = 0.0423 and 0.0043, respectively). TFS was significantly shorter in patients with NLR ≥2.21 in the following subgroups: sporadic schwannoma, primary schwannoma, schwannoma ≥30 mm in size, subtotal resection, vestibular schwannoma, and postoperative recurrence. Conclusions Preoperative NLR ≥2.21 before surgery was significantly associated with retreatment after schwannoma resection. NLR may be a novel predictor of retreatment and assist surgeons in preoperative surgical decision making.